Irony and Humour in Frances Burney's Novels - Slováková, Dagmar (Univerzita Pardubice, 2014)
The main purpose of this paper is to provide an analysis of irony and humour in two novels Evelina and Camilla written by a novelist Fanny Burney in the second half of the 18th century and compare them to a novel Pride and Prejudice from a novelist Jane Austen. Their works provide us information about middle and upper class of contemporary society, about their view on the society, following social rules through individual characters and different situations. Each character is studied from various aspects according to his or her role in heroine's life. Sometimes humorous situations are included that usually happen due to character's ignorance or low intelligence. The thesis also briefly describes lives of the two heroines in order to more understand the whole plot and the analysis. Fanny Burney was the great inspiration to a later famous novelist Jane Austen who wrote her novels in very similar style.
Ironie a Humor v románech Frances Burneyové
Keywords: Burney, Fanny; ironie; humor; charakter; etika; společnost; Austen, Jane; irony; humour; characters; morality; society